Cancer treatment-induced bone loss - Yong Jun Choi (The Korean Journal of Internal Medicine, 2024)
Cancer treatment-induced bone loss (CTBL) is associated with anti-tumor treatments, including endocrine therapies, chemotherapeutic treatments, radiotherapy, glucocorticoids, and tyrosine kinase inhibitors. Osteoporosis, characterized by the loss of bone mass, can increase the risk of fractures, leading to mortality and long-term disability, even after cancer remission. Cancer and osteoporosis have marked clinical and pathogenetic similarities. Both have a multifactorial etiology, affect the geriatric population, and markedly influence quality of life. Lifestyle management, including calcium and vitamin D supplementation, is recommended but the supporting evidence is limited. Oral and injectable bisphosphonates are effective for osteoporosis and malignant bone disease. Bisphosphonates increase bone mineral density (BMD) in patients with CTBL. Denosumab is also used in the management of CTBL; in clinical trials, it improved BMD and reduced the risk of fracture. Currently, there are no bone anabolic therapies for patients with cancer. Appropriate therapies are necessary to maintain optimal bone health, particularly in patients at heightened risk.